Airway smooth muscle function in asthma - Xiong, Dora (Jun Ping); Martin, James G.; Lauzon, Anne-Marie (Frontiers in Physiology, 2022)
Known to have affected around 340 million people across the world in 2018, asthma is a prevalent chronic inflammatory disease of the airways. The symptoms such as wheezing, dyspnea, chest tightness, and cough reflect episodes of reversible airway obstruction. Asthma is a heterogeneous disease that varies in clinical presentation, severity, and pathobiology, but consistently features airway hyperresponsiveness (AHR)—excessive airway narrowing due to an exaggerated response of the airways to various stimuli. Airway smooth muscle (ASM) is the major effector of exaggerated airway narrowing and AHR and many factors may contribute to its altered function in asthma. These include genetic predispositions, early life exposure to viruses, pollutants and allergens that lead to chronic exposure to inflammatory cells and mediators, altered innervation, airway structural cell remodeling, and airway mechanical stress. Early studies aiming to address the dysfunctional nature of ASM in the etiology and pathogenesis of asthma have been inconclusive due to the methodological limitations in assessing the intrapulmonary airways, the site of asthma. The study of the trachealis, although convenient, has been misleading as it has shown no alterations in asthma and it is not as exposed to inflammatory cells as intrapulmonary ASM. Furthermore, the cartilage rings offer protection against stress and strain of repeated contractions. More recent strategies that allow for the isolation of viable intrapulmonary ASM tissue reveal significant mechanical differences between asthmatic and non-asthmatic tissues. This review will thus summarize the latest techniques used to study ASM mechanics within its environment and in isolation, identify the potential causes of the discrepancy between the ASM of the extra- and intrapulmonary airways, and address future directions that may lead to an improved understanding of ASM hypercontractility in asthma.